Production of Mycoblock from the Mycelium of the Fungus Pleurotus ostreatus for Use as Sustainable Construction Materials - Digafe Alemu; Mesfin Tafesse; Yohannes Gudetta Deressa (Advances in Materials Science and Engineering)
As the global population rises, resource depletion and environmental pollution also aggravate. To meet the needs of the population, different products have been manufactured. However, most industrially manufactured products are not eco-friendly, costly, and locally unavailable. To solve these problems, using and enhancing locally available biomaterials are the key option. Three substrates sawdust, bagasse, and coffee husk and the fungus Pleurotus ostreatus were used. Mycelium was fully colonized by 9, 14, and 27 days on potato dextrose agar (PDA), sorghum grain, and substrate, respectively. The mycelium growth on coffee husk showed the fastest growth rate whereas that of the sawdust was slowest. The fully colonized substrates were molded for 7, 14, and 21 days by plastic mold to maintain their regular 3D structure. The result shows that the block made with sawdust at 21 molding period has higher compressive strength and density of 750 kPa and 343.44 Kg/m3, respectively, followed by bagasse and coffee husk. These variations were due to the mycelium density difference between the substrates. Physicochemical and mechanical characteristics such as mycelium morphology, bimolecular and elemental analysis of substrates, density, water absorption, and compressive strength of the block were analyzed. This technology has the potential to replace conventional construction and packaging materials used for indoor applications such as insulation, partition walls, and other design and architectural applications. It also benefits in terms of its low cost, green synthesis approach, nontoxicity, low environmental emission, recyclability, and local availability.